DETERMINAN NYERI PUNGGUNG BAWAH PADA APARATUR SIPIL NEGARA DI LINGKUNGAN DINAS KESEHATAN KABUPATEN SEKADAU - Juliansyah, Elvi; Sumitra, Rahmat; Sunarti, Sunarti; Damayanti, Ria; Yuanita Pratama, Rika (NHM PRESS, 2024)
Low back pain (LBP) is a common health problem experienced by workers in various sectors, including in the Health Service. In Sekadau Regency, this condition is a concern because it can have a direct impact on work productivity, quality of health services, and employee welfare. The results of the statistical test showed no significant relationship between age and lower back pain. The statistical test obtained a p value of 1,000> (p value = 0.05), there was a significant relationship between body weight and lower back pain with a p value of 0.001 < (p value = 0.05) and an OR value of 5.762, there was a significant relationship between knowledge and lower back pain with a p value of 0.005 < (p value = 0.05) and an OR value of 3.810, there was no significant relationship between sitting position and lower back pain with a p value of 1,000> (p value = 0.05), there was a significant relationship between length of service and lower back pain with a p value of 0.010 < (p value = 0.05) and an OR value of 3.567. It can be concluded that body weight, knowledge, and length of service are related to the incidence of lower back pain in Civil Servants in the Sekadau Regency Health Office. It is recommended that body weight should be maintained to remain stable and can support the body by increasing knowledge about back pain in Civil Servants with more than 10 years of service.